In Search of a Theory of Deference: The Eighth Amendment, Democratic Pedigree, and Constitutional Decision Making - Eric Berger (Washington University Law Review, 2010)
The Supreme Court’s recent Eighth Amendment death penalty case law is in disarray, and the confusion is symptomatic of a larger problem in constitutional doctrine. In Baze v. Rees and Kennedy v. Louisiana, the Court approached the challenged state policies with vastly different levels of deference. Though the Court purported to apply longstanding Eighth Amendment tests in both cases, Baze was highly deferential to state policy, and Kennedy was not deferential at all. Remarkably, neither the Court nor legal scholars have acknowledged, let alone justified, these contrasting approaches. This Article proposes a theory of deference to address this discrepancy. Courts often premise deference in constitutional cases on political authority and epistemic authority. While these rationales make sense in theory, courts sometimes mechanically repeat them without asking whether the responsible institution enjoys either kind of authority in reality. Courts should engage in such inquiries before summarily granting or denying deference. In light of these principles, the Court approached the problems of deference in Baze and Kennedy carelessly. Whereas Baze assumed (without explanation) that the state possessed political and epistemic authority worthy of deference, Kennedy assumed (also without explanation) the exact opposite. Attention to these issues in the Eighth Amendment and other constitutional contexts would encourage more transparent, deliberative policymaking and more careful, candid judicial-constitutional decision making.
Keywords: Eighth amendment protections (United States Constitution); Judicial process; Judicial deference; Capital punishment; Constitutional law